2020
DOI: 10.1136/annrheumdis-2020-218479
|View full text |Cite
|
Sign up to set email alerts
|

Historically controlled comparison of glucocorticoids with or without tocilizumab versus supportive care only in patients with COVID-19-associated cytokine storm syndrome: results of the CHIC study

Abstract: ObjectivesTo prospectively investigate in patients with severe COVID-19-associated cytokine storm syndrome (CSS) whether an intensive course of glucocorticoids with or without tocilizumab accelerates clinical improvement, reduces mortality and prevents invasive mechanical ventilation, in comparison with a historic control group of patients who received supportive care only.MethodsFrom 1 April 2020, patients with COVID-19-associated CSS, defined as rapid respiratory deterioration plus at least two out of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
211
1
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(244 citation statements)
references
References 17 publications
13
211
1
19
Order By: Relevance
“…Similarly, Toniati et al also showed that tocilizumab can improve the prognosis of COVID‐19 patients with ARDS, ferritin, CRP, and fibrinogen levels that steadily decrease after 10 days of tocilizumab treatment 82 . Ramiro et al observed that patients with COVID‐19‐associated cytokine storm syndrome treated by tocilizumab and glucocorticoids have better treatment benefit, especially those with serum ferritin levels above the median value of 1419 µg/L 83 . However, Pérez‐Sáez et al found that the level of CRP rather than the one of ferritin decreases after tocilizumab treatment in patients who need kidney transplant, and the decrease is positively related to survival 84 …”
Section: Resultsmentioning
confidence: 92%
“…Similarly, Toniati et al also showed that tocilizumab can improve the prognosis of COVID‐19 patients with ARDS, ferritin, CRP, and fibrinogen levels that steadily decrease after 10 days of tocilizumab treatment 82 . Ramiro et al observed that patients with COVID‐19‐associated cytokine storm syndrome treated by tocilizumab and glucocorticoids have better treatment benefit, especially those with serum ferritin levels above the median value of 1419 µg/L 83 . However, Pérez‐Sáez et al found that the level of CRP rather than the one of ferritin decreases after tocilizumab treatment in patients who need kidney transplant, and the decrease is positively related to survival 84 …”
Section: Resultsmentioning
confidence: 92%
“…The aforementioned concerns remain to be further clarified in upcoming TCZ randomized control trials [ 48 , 49 ]. Recently, a therapeutic regime involving a course of high-dose methylprednisolone, followed by TCZ if needed, showed that it may accelerate respiratory recovery, reduce hospital mortality and the rate of invasive mechanical ventilation in COVID-19-associated cytokine storm syndrome [ 50 ]. Of note, the preliminary findings of a phase III global TCZ versus placebo study (EMPACTA) showed that the administration of TCZ in patients with COVID-19 associated pneumonia plus standard of care were 44% less likely to progress to mechanical ventilation or death compared to patients who received placebo plus standard of care [(log-rank p-value = 0.0348; hazard ratio (95% CI) = 0.56 (0.32, 0.97)] [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective case-series has several limitations, which prevent its generalizability. First, our patients might have improve to concomitant empiric antiviral and steroid therapy [ 4 , [7] , [8] , [9] , [10] , 30 , 47 , 50 ]. However, given the severity of their clinical status, the administration of TCZ might have helped by mitigating a full blown picture of hyperinfammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive immunosuppressive treatment with high dose glucocorticoids, followed by an interleukin-6 (IL-6) receptor antagonist where needed, accelerates respiratory recovery and reduces deaths in patients with covid-19-associated cytokine storm syndrome (CSS), an observational study1 has shown.…”
mentioning
confidence: 99%